INTERCULTURAL AND INCLUSIVE SCHOOLS AS AN ALTERNATIVE TO THE EDUCATION CRISIS IN COLOMBIA - Ortega Mejía, David Alberto
The reality of the official school in Colombia has been shaped around populations characterized by poverty and inequality indices, includingthat many of the territories have witnessed a political and economic struggle that has relegated education to the background; To this, he adds that the efforts of the national government have been focused on compliance with international standards, which is why the educational community has been appointed to achieve the best results despite its limitations and difficulties. In this sense, the purpose of this article is to analyze the aspects that obviously affect the Colombian school, also allowing the intercultural and inclusive school to be exposed as an alternative for change and improvement. The intercultural school proposal arises in response to the changes presented worldwide and that have made inclusion as a benchmark for guaranteeing rights for increasingly interconnected, democratic and pluralistic societies.